Factors related to the Attitude of Pregnant Women in Covid 19 Vaccination - Risqi Dewi Aisyah; Fitriyani (Universitas STRADA Indonesia, 2022)
Covid-19 vaccination during pregnancy does not cause significant vaccine-related side effects or side effects resulting or adverse outcomes of obstetrics, fetuses, or neonatal outcomes. Concerns have been raised about the potential spike in Covid-19 in pregnancy, secondary to the increasing number of Covid-19 in the community, the easing of social restrictions, and doubts about vaccination. The purpose of this study is to find out the factors related to the attitude of pregnant women in carrying out Covid-19 vaccination. This descriptive study uses a cross-sectional method to analyze the data. The participants in this study were 155 pregnant women with a gestational age over 13 weeks who were scheduled to receive the first jab of Covid-19 vaccine. A total of 155 pregnant women were included in this study's sample. Logistic regression was employed in the statistical analysis.